Human Diversity in Education : an Integrative Approach - Cushner, Kenneth; McClelland, Averil; Safford, Philip (McGraw-Hill Boston ; Toronto, 2000)
This text addresses the preparation of teachers for the various forms of human diversity they are certain to meet in their classrooms, schools and communities, including that of nationality, ethnicity, race, religion, gender, class, language, sexual orientation and ability levels.
Including Illustration and Index
Keywords: Multicultural education -- Sex differences in education -- Individual differences in children